Comparison on the Growth Variability of Vibrio parahaemolyticus Coupled With Strain Sources and Genotypes Analyses in Simulated Gastric Digestion Fluids - Wang, Yangmei; Zhao, Yong; Pan, Yingjie; Liu, Haiquan (Frontiers in Microbiology, 2020)
Vibrio parahaemolyticus is a food-borne pathogen causing pathogenic symptoms such as diarrhea and abdominal pain. Currently no studies have shown that pathogenic and non-pathogenic V. parahaemolyticus has growth heterogeneity in human environment such as gastric and intestinal fluid. This study firstly uses simulate human gastric fluid to explore growth variability of 50 strains of V. parahaemolyticus, which was determined at 37 °C. The growth curve was fitted by primary modified Gompertz model and the maximum growth rate (μmax) and lag time (LT) were calculated to compare the growth characteristics of all V. parahaemolyticus strains. The results showed that there were significant differences in μmax and LT between pathogenic and non-pathogenic V. parahaemolyticus. Thereinto, the μmax of pathogenic strains was higher than that of non-pathogenic strains. Conversely, the μmax of non-pathogenic group was lower than that of non-pathogenic group. In addition, the LT of pathogenic strains was shorter than that of non-pathogenic strains. As a result, pathogenic strains had the characteristics of fast growth rate and short lag time, implying that the activities of the strain and enzyme system are enhanced. The research demonstrates that a safe insight into the research and effective control of pathogenic V. parahaemolyticus risk assessment. And provide effective information for humans to mitigate the risk of disease prevention and control.